2007
DOI: 10.1021/jo062117x
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of Pyridine Deprotonation in the Gas Phase

Abstract: The regioselective deprotonation of pyridine in the gas phase has been investigated by using chemical reactivity studies. The mixture of regioisomers, trapped as carboxylates, formed in an equilibrium mixture is determined to result from 70-80% deprotonation in the 4-position, and 20-30% deprotonation at the 3-position. The ion formed by deprotonation in the 2-position is not measurably deprotonated at equilibrium because the ion is destabilized by lone-pair repulsion. From the composition of the mixture, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 60 publications
8
33
0
Order By: Relevance
“…Moreover, Yamamoto has reported that 2,5‐dibromo‐6‐hexylpyridine also afforded only 5‐chloromagnesio pyridine in the reaction with i PrMgCl 7. These results can be accounted for by the fact that the chloromagenesio group at the 2‐position would suffer repulsion from the lone pair of the nitrogen of the pyridine ring 17. In the reaction of 1 with i PrMgCl, however, coordination of the oxygen of the MEEO group to magnesium would promote the bromo‐chloromagnesio exchange reaction at the 2‐position to some extent, to afford 2‐chloromagnesiopyridine 7 as a minor product 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Yamamoto has reported that 2,5‐dibromo‐6‐hexylpyridine also afforded only 5‐chloromagnesio pyridine in the reaction with i PrMgCl 7. These results can be accounted for by the fact that the chloromagenesio group at the 2‐position would suffer repulsion from the lone pair of the nitrogen of the pyridine ring 17. In the reaction of 1 with i PrMgCl, however, coordination of the oxygen of the MEEO group to magnesium would promote the bromo‐chloromagnesio exchange reaction at the 2‐position to some extent, to afford 2‐chloromagnesiopyridine 7 as a minor product 18…”
Section: Resultsmentioning
confidence: 99%
“…7 These results can be accounted for by the fact that the chloromagenesio group at the 2-position would suffer repulsion from the lone pair of the nitrogen of the pyridine ring. 17 In the reaction of 1 with i PrMgCl, however, coordination of the oxygen of the MEEO group to magnesium would promote the bromo-chloromagnesio exchange reaction at the 2-position to some extent, to afford 2-chloromagnesiopyridine 7 as a minor product. 18 Polymerization and Polymer Structure Polymerization of Grignard monomer 6 and 7, generated from 1 with i PrMgCl, was carried out by addition of 1.8 mol % Ni(dppp)Cl 2 to the reaction mixture, as in the case of the polymerization of Grignard alkylthiophene monomers, 2 but a yellow solid was unexpectedly precipitated within 1 h. The polymerization, however, was continued for 3 h (Scheme 3).…”
Section: Synthesis Of Monomer Precursor and Generation Of Grignard-tymentioning
confidence: 99%
“…To further explore the substituent effect of the N-oxide in the ring, we have turned to an analysis developed by Schafman and Wenthold 11. Using the established relationship between resonance and field effects determined by Taft for benzoic acids in the gas phase (Equations 1 and 2), it is possible to extract pseudo-Hammett parameters for the ring N-oxide 20.…”
Section: Discussionmentioning
confidence: 99%
“…Deprotonated pyridine has an experimental PA of 389.9 kcal/mol11 and therefore oxidation decreases the ΔH acid of pyridine by about 10 kcal/mol. Schafman and Wenthold have analyzed positional acidities in pyridine in detail and has found that the para position is slightly more acidic than the meta position, and both are much more acidic than the ortho position11. To allow for a fair comparison, we have recomputed the positional acidities of pyridine at the G3MP2 level (Table 1, Scheme 2) and the values are consistent with Wenthold’s work.…”
Section: Discussionmentioning
confidence: 99%
“…It must be mentioned, however, that one of the main drawbacks of the proton abstraction method is its poor selectivity when there is more than one deprotonation site with comparable acidity in the molecule. For example, Schafman and Wenthold (2007) showed that in the gas-phase reaction of pyridine with OH À ion, 3-and 4-pyridide ions are formed in an approximately 1:4 ratio. Therefore, the deprotonation method gives information about the thermodynamics of the carbanion formation reactions, which makes it very useful, for example, in proton affinity (PA) measurements.…”
Section: Proton Transfer Reactionsmentioning
confidence: 99%